CONTEXTUAL LEARNING APPROACH AND PERFORMANCE ASSESSMENT IN MATHEMATICS LEARNING - I Wayan Eka Mahendra (LPPM Universitas Negeri Jakarta, 2015)
This study aims to determine the effect of formative assessment and learning approach to the mathematics learning outcome after controlling the numerical aptitude. It was a quasi-experiment with a sample of 186 students obtained by using multistage random sampling technique with 2x2 factorial designs. The data were analyzed by ANCOVA. After controlling the numerical aptitude, the results are: the mathematics learning outcome of the students who followed a contextual approach was better than the ones who followed a conventional learning approach, the mathematics learning outcome of the students who were given a performance assessment was better than the ones who were given a conventional assessment, the interaction between the learning approach and formative assessment affected the students learning outcome for mathematics, the students who followed a contextual learning approach were more suitable to be given a performance assessment, whereas the ones who followed a conventional learning approach were more appropriate to be given a conventional assessment. Based on the research findings, junior high school teachers are suggested to improve their students learning outcome for mathematics. Then, teachers need to use a learning approach and formative assessment accurately and correctly.